Socioeconomic and Demographic Determinants of Husband's Involvement in Antenatal Care in Coastal Areas of Bandar Lampung City - Daeli, Jul Hasratman; Fatriani, Rully (Journal of Midwifery, 2024)
This study aims to identify socioeconomic and demographic factors influencing husband involvement in Antenatal Care (ANC) in the coastal areas of Bandar Lampung, where such involvement is often limited. Using an observational analytic approach with a cross-sectional design, the study involved 170 pregnant women from coastal areas and assessed factors like husband’s age, education level, number of children, and employment status through structured questionnaires. The findings revealed significant associations between husband involvement in ANC and both age (p-value 0,0137) and education level (p-value 0,0000), while the number of children and employment status showed no significant correlation. Policymakers should pay more attention to the issue of husband involvement in ANC in Bandar Lampung’s coastal areas. Improving access to and the quality of formal education in these areas is expected to improve cultural perceptions and welfare levels, thereby increasing husband involvement in antenatal care